On the Nature of Quality in the Contexts of Academic Publication and Sustainability - Shephard, Kerry; Thondhlana, Gladman; Wolff, Lili-Ann; Belluigi, Dina Zoe; Rieckmann, Marco; Vega-Marcote, Pedro (Frontiers in Education, 2021)
Six experienced academic reviewers and editors explored the nature of quality in academic publication processes in the contexts of sustainability, education for sustainability and the Sustainable Development Goals. This article documents their exploration as a collaborative autoethnography structured around authors’ personal reflections on matters such as: how current quality indicators define the quality of academic publications; how effective current quality assurance processes may be; how congruent open-access publication processes may be with the ideals of sustainability and of the Sustainable Development Goals; and on what new and different indicators of quality might look like. An inductive analysis of their reflections yielded three emergent and reoccurring themes; casting doubt on the fitness for purpose of current academic publication processes and means to assure their quality, seeking justice for all involved in academic publication, and creating opportunities for change. In writing this article, authors considered these themes and how academia might address them.